Nutrition and Fertilization of Palms in Containers - Timothy K. Broschat (EDIS)
Palms growing in containers are susceptible to the same deficiencies that landscape palms experience, but the relative importance of the various deficiencies as well as their causes are different. Container substrates are generally more acidic and have greater nutrient-holding capacity than Florida native soils. Thus leaching and insolubility of nutrients are much less of a problem. Also, container-grown palms are often fertilized with more complete controlled-release fertilizers or regular liquid fertilization, which prevents most deficiencies from occurring. This document is ENH1010, one of a series of the Department of Environmental Horticulture, UF/IFAS Extension. Original publication date September 2005.